Residual Stresses and Cracking in Dental Restorations due to Resin Contraction Considering In-Depth Young's Modulus Variation - Casas, Estevam Barbosa de Las; Jr., João Batista Novaes; Talma, Elissa; Vasconcelos, Willian Henrique; Cornacchia, Tulimar P. Machado; Braga, Iracema Maria Utsch; Jr., Carlos Alberto Cimini; Peixoto, Rodrigo Guerra (IntechOpen, 2012)
None